Analisis Struktural Dan Relevansi Pembelajaran Bahasa Indonesia Pada Novel Emak Karya Daoed Joesoef - Nikmah, Faridhatun (Lingua, 2020)
This study aims to describe (1) the intrinsic element of Daoak Joesoef's Emak Karya novel, and (2) its relevance in learning. This research is a descriptive qualitative study with a novel content analysis method. The results showed that: (1) Structural analysis, the theme of the novel Emak is the story of the relationship of eternal affection between a child and mother, the plot used is a forward path, characterization in the Emak novel is divided into three namely protagonists, antagonists, and extras. The point of view used is the viewpoint of the third person as the main character. The background used is the setting of the place, time and atmosphere. The dominant language style used by authors is parerelism, metaphor, symbolic, paradox, and association. The mandate used is written from the contents of the novel; and (2) Relevance as teaching material for class X high school.Ã‚Â